The Festivity of Maulid Nabi in Cikoang, South Sulawesi: Between Remembering and Exaggerating the Sprit of the Prophet - Muhammad Adlin Sila (Studia Islamika, 2001)
This article traces the problems of religious distinctiveness in a stratified community in the village of Cikoang on the south coast of South Sulawesi. With a population of approximately in most respects a typical Makassarese village (Source: Cikoang Dalam Angka 1994) The inhabitants calim to be Shafi'i Muslims (a school of Islamic Law within the Sunni branch of Islam), and have altogether a similar historical tradition.DOI: 10.15408/sdi.v8i3.680